Typology of the family system and conflict dynamics viewed through the experiences of the child - Evgeniya Yordanova-Karageorgieva; Boryana Chalakova (The Global Psychotherapist)
The present exposition is aimed at the family typology as part of the psychotherapeutic diagnostics of conflict dynamics within the family. The family psychotherapy focuses on the family system as an object of unique characteristics. More than other family members, children are likely to react to disruptions in family relationships with emotional or behavioral disorders and dysfunctions. For this reason, psychotherapeutic work with children is often a significant point for diagnosing family conflict dynamics. The present study describes our psychotherapeutic work experience with children from different family environments. For the purposes of the study, we categorized the individual types of family systems according to their specificities. We have structured these according to the leading existential fear and impulse, so four basic types of family have been identified – schizoid, depressive, compulsive, and histrionic. Specific conflict dynamics for each type are presented using cases from our practice. Therapeutic guidelines can be formulated based on these to help the psychotherapeutic process.